Mesenchymal stem cell-derived interleukin-28 drives the selection of apoptosis resistant bone metastatic prostate cancer - Jeremy J. McGuire (Nature Portfolio, 2021)
The effects of bone-marrow derived MSCs on prostate cancer cells remain unknown. Here the authors show that MSC-derived IL-28 induces prostate cancer cell apoptosis via IL-28Rα-STAT1 signalling, while acquired resistance to apoptosis is associated with a shift in IL-28Rα signalling via STAT1 to STAT3.